Comparison of teeth discolorations induced by Mineral trioxide aggregate, Calcium-enriched mixture and Biodentine using spectrophotometric analysis - Azin Jamshidifar (Caspian journal of dental research, 2019)
Introduction:Most of the materials used in endodontic procedures may lead to discoloration.This study compared the discolorations induced following treatment by MTA, CEM ,and Biodentine using a spectrophotometric analysis. Materials&Methods:In this experimental study Forty extracted mandibular anterior teeth were selected and sectioned from 2 mm below Cemento Enamel Junction(CEJ) using a disc. A retrograde method was used for drilling cavities 2 mm away from incisal edge. Then the cavities were washed using 5.25% NaOCL and normal saline and the samples were divided randomly into 4 groups. The cavities in groups 1, 2, and 3 were filled by MTA Angleus, Cem cement, and Biodentine, respectively as deep as CEJ level and they were sealed by 2mm of A3 composite color. All of cavities of group 4/control, were all filled by composite A3. Then the samples were stored in a glass incubator with 100% humidity and  under laboratory light .they were exposed to a spectrophotometric analysis within 6 periods from placement including base line, 1 week, 2 weeks, 1 month, 3 months, 6 months. The data were analyzed by SPSS 17 ,Tukey HSD and ANOVA statistical test. Results:The results showed no statistically significant difference in discoloration rate during measurement periodsin each group. However, the discoloration rate varied in various materials. The minimum and maximum discolorations occurred in Biodentine and MTA, respectively and their difference was statistically significant.(p=0.033)Other groups showed no statistically significant difference. Conclusion: The biodentinehad minimum discolorations compared with other two materials; thus, it seems that it can be recommended for cosmetic areas.